Exceptionally preserved Leptolepidae (Actinopterygii, Teleostei) from the late Early Jurassic Fossil-Lagerstätten of Grimmen and Dobbertin (Mecklenburg-Western Pomerania, Germany) - Konwert, Martin; Stumpf, Sebastian (Zootaxa, 2017)
Exceptionally well-preserved fishes of the family Leptolepidae (Actinopterygii, Teleostei) from the late Early Jurassic Fossil-Lagerstätten of Grimmen and Dobbertin (Mecklenburg-Western Pomerania, NE Germany) are reported and detailed anatomical descriptions are given. The described material specifically derives from the “Green Series”, which represents a specific facies that falls within the lower part of the early Toarcian Harpoceras falciferum ammonite Zone. Complete skeletons are rare, and most specimens are represented by isolated skulls. Most of the skulls are fully articulated and show only a low degree of compaction, while some specimens are almost three-dimensionally preserved. The leptolepid fauna comprises Leptolepis coryphaenoides, L. normandica, L. jaegeri, a possible Proleptolepis, and two other taxa, which are described in open nomenclature. Several anatomical characters, such as the shape of premaxilla, maxilla, dentary, preopercle, the cephalic sensory canals, and the dentition of the jaws, are discussed and compared to former studies. The new material provides novel insights into morphology, diversity and palaeobiogeography of leptolepid fishes. The records of Leptolepis coryphaenoides, L. normandica and L. jaegeri from Grimmen and Dobbertin represent the northeastern-most occurrences of these species from Europe, suggesting that they inhabited the whole central European epicontinental sea during the early Toarcian. The possible occurrence of Proleptolepis in the lower Toarcian of Grimmen suggests that this genus might have had a much wider palaeobiogeographical and temporal distribution, since specimens attributed to Proleptolepis have previously been reported only from the Sinemurian of western Europe.